Ru(bpy)32+ derivatized polystyrenes constructed by nitroxide-mediated radical polymerization. Relationship between polymer chain length, structure and photophysical properties. Issue 47 (9th October 2015) - Leem, Gyu; Keinan, Shahar; Jiang, Junlin; Chen, Zhuo; Pho, Toan; Morseth, Zachary A.; Hu, Zhenya; Puodziukynaite, Egle; Fang, Zhen; Papanikolas, John M.; Reynolds, John R.; Schanze, Kirk S.
Abstract : A series of polystyrene-based light harvesting polymers featuring pendant polypyridyl ruthenium complexes has been synthesized. Abstract : A series of polystyrene-based light harvesting polymers featuring pendant polypyridyl ruthenium complexes has been synthesized. The polymer backbones were prepared by nitroxide-mediated radical polymerization with a variable average molecular weight ( M n ) ranging from ∼5500 to ∼24 000 g mol −1 . Pendant Ru(ii ) polypyridyl complexes were grafted to the polymer backbone by azide–alkyne click chemistry to afford chromophore loaded polymers. The resulting polystyrene-based polychromophores with pendant Ru(ii ) polypyridyl complexes (PS-Ru) were characterized by nuclear magnetic resonance and infrared spectroscopy, confirming the high efficiency of the click grafting. The photophysical and electrochemical properties of the series of PS-Ru polymers were characterized in solution and investigated as a function of polymer chain length and solvent. The electrochemical properties of PS-Ru maintained the characteristics of the individual Ru(ii ) polypyridyl units. Emission quantum yield and lifetime studies reveal that the metal-to-ligand charge transfer (MLCT) excited states are quenched to a variable extent depending on the molecular weight of the polymers, consistent with intramolecular energy transfer and self-quenching in polymers with longer chain lengths. To support the synthetic effort, molecular dynamics simulations of the polypyridyl ruthenium derivatized polystyrenes in different solvents were conducted.